2022
DOI: 10.3991/ijim.v16i18.32657
|View full text |Cite
|
Sign up to set email alerts
|

Google Classroom Amidst COVID-19 Pandemic in Indonesian Elementary Schools: Teachers’ Perceptions and Motivation

Abstract: Google Classroom seems to be one of the most trending platforms used in secondary and tertiary levels but it has been observed to be rarely applied in elementary schools, and therefore the research about it is also still limited. This study was intended to give an insight of how effective this e-learning platform is utilized in supplementing the Elementary school teachers’ instructional programs by investigating their perceptions and motivation. Via the quantitative method of a questionnaire survey, the resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The majority of teachers are reported to have insufficient technological proficiency, with a particularly noticeable deficit noted in rural areas [16], [17]. Although various applications and tools have been developed to support teachers in online teaching, WhatsApp has emerged as the preferred platform widely used in educational institutions in this country due to its simplicity, practicality, and affordability [12], [18][19][20]. However, while WhatsApp facilitates a dynamic learning environment, it is widely recognized that this application may not be sufficient to meet the demands of a comprehensive and effective teaching and learning experience, primarily due to its limited facilities and features.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of teachers are reported to have insufficient technological proficiency, with a particularly noticeable deficit noted in rural areas [16], [17]. Although various applications and tools have been developed to support teachers in online teaching, WhatsApp has emerged as the preferred platform widely used in educational institutions in this country due to its simplicity, practicality, and affordability [12], [18][19][20]. However, while WhatsApp facilitates a dynamic learning environment, it is widely recognized that this application may not be sufficient to meet the demands of a comprehensive and effective teaching and learning experience, primarily due to its limited facilities and features.…”
Section: Introductionmentioning
confidence: 99%
“…The study aims to learn how intention to use a personal learning environment based on Google applications for supporting collaborative learning is formed, in the context of university student learning [29]. The use of online facilities using the Google platform can be considered because there are positive perceptions and increase teacher motivation in utilizing online learning [30].…”
Section: Introductionmentioning
confidence: 99%
“…15, 2020) In Indonesia, including West Kalimantan, Moodle as a learning media is not as widely used as it is in other countries (Gamage et al, 2022;Folden, 2011). Most learnings in many areas in this country, especially in West Kalimantan, use Google Classroom, which was found to be easier and more practical than other learning webs or apps (Suparjan & Ismiyani, 2022). Several instances of the use of MOODLE were reported at SMA Muhammadiyah 2 Yogyakarta (Rahmani, 2021), which revealed that MOODLE encourage students' interest in learning and greatly contribute to improving students' competence in the use of technology and pedagogy in learning English.…”
Section: Introductionmentioning
confidence: 99%